COMPARISON OF CARBON STOCK BASED ON EXISTING LAND COVER AND SPATIAL PATTERN PLANS IN GILI MATRA - Siska Ita Selvia; Zuhdiyah Matienatul Iemaaniah (GeoEco, 2024)
As a mainstay destination on Lombok Island, Gili Matra has many strategic issues for which appropriate and effective solutions still need to be found. Massive changes in land use for tourism activities, land use conflicts, land sales on small islands to foreign nationals, environmental damage, and pollution. This condition will gradually lead to land use outside its intended use. Through the North Lombok PUPR (Public Work and Public Housing) Department Service and various related stakeholders, the government prepared the Detailed Spatial Plan (RDTR) for the Gili Tramena Tourism Area to anticipate land use different from sustainable spatial planning principles. This research compares the potential carbon stored in existing land cover and the polar money plan in Gili Matra (Meno, Trawangan, and Air) based on the RDTR for the Gili Tramena Tourism Area. The method used is gap analysis or deviation of existing land cover with spatial pattern plans on Gili Matra using overlay techniques. It also uses a conversion method for carbon stock estimates between existing land use and planned spatial patterns on Gili Matra. The results of this research are a decrease in carbon stocks in the spatial pattern plan (2,616.75 tons C) compared to carbon stocks based on existing land use classes on Gili Matra (12,571.24 tons C). This research shows that there is a difference of 9,954.49-ton C. Therefore, appropriate recommendations include: 1) provide a minimum of 30% of the land for Green Open Space (RTH); 2) maximizing protected zones; 3) carry out supervision and control in zones designated as protected zones; and 4) developing the concept of sustainable tourism.